2010
DOI: 10.1093/eurpub/ckq017
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use prevalence, knowledge and attitudes among Italian hospital healthcare professionals

Abstract: Among Italian hospital personnel there is a paradoxically large prevalence of smokers, higher than in the general population. Interventions aimed for the development of an adequate culture of health promotion, among these professionals, are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 17 publications
3
50
0
5
Order By: Relevance
“…In another study mean age of the respondents were 37.3 years. 20 Majority of the respondents (55.9%) had monthly family income of Taka 10001-20000 and the average monthly family income was Tk. 12776.54 ± 5230.13.…”
Section: Discussionmentioning
confidence: 99%
“…In another study mean age of the respondents were 37.3 years. 20 Majority of the respondents (55.9%) had monthly family income of Taka 10001-20000 and the average monthly family income was Tk. 12776.54 ± 5230.13.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Nurses play significant key roles in tobacco use prevention and cessation interventions. [4] While studying at academic settings, nursing students develop their professional roles in giving help to smokers who wish to quit. Consequently, it is pressingly necessary to explore tobacco smoking history and behaviors, knowledge, attitudes, and beliefs towards smoking among nursing students, and to have an insight into the nature of education they receive on smoking cessation.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…In 2012, more than a quarter of the population of 15 to 64 years was a tobacco consumer [4][5][6][7][8][9][10][11][12]. The majority of Portuguese started smoking consumption between 12 and 20 years of age, largely due to the influence of friends or curiosity and willingness to experiment.that it is imperative to invest in prevention and control of this important national public health problem [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that as smoking rates decline among physicians, a similar reduction will be observed in the general population as well. Recent data demonstrated that surgical specialities have greater tendency to stress with more highest percentage of smokers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%